2010
DOI: 10.1590/s0004-27302010000700004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of central obesity in a large sample of adolescents from public schools in Recife, Brazil

Abstract: Objective: To determine the prevalence and association of central obesity (CO) and hypertension and its associations with alcohol intake, smoking and physical activity in adolescents. Subjects and methods: Cross sectional study in 1,824 students from 29 public schools in Recife. Results: 89.6% were normal weight, 6.7% overweight and 3.7% obese; 77.2% were normotensive, 5.9% prehypertensive and 16.9% hypertensive; CO was 10.2% when the 90 th percentile was used as cutoff and 25.2% when the 75 th percentile was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
1
10
0
5
Order By: Relevance
“…Thus, our findings support previous research in which overweight in adolescents was not associated with alcohol consumption (Peltzer & Pengpid, 2011), but our findings contrast with other studies that observed this association (Croezen, et al, 2009;Griz et al, 2010). As highlighted by Alfonso and colleagues (2009) the intimate relationships between peers is also a powerful predictor of youth's involvement on the use of alcohol.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, our findings support previous research in which overweight in adolescents was not associated with alcohol consumption (Peltzer & Pengpid, 2011), but our findings contrast with other studies that observed this association (Croezen, et al, 2009;Griz et al, 2010). As highlighted by Alfonso and colleagues (2009) the intimate relationships between peers is also a powerful predictor of youth's involvement on the use of alcohol.…”
Section: Discussionsupporting
confidence: 86%
“…This association has also been established by several researchers [28,61,94,[100][101][102][103][104][105][106]. Some of these studies showed that this association was stronger in boys than in girls [104][105][106], and the association of AO with systolic hypertension have been seen more frequently than with diastolic hypertension [107,108]. In a recent systematic review by Kelishadi et al, they found only one study showing that total body fat is a stronger predictor of elevated BP than AO in children and adolescents [28,109].…”
Section: Hypertensionmentioning
confidence: 58%
“…In a recent trial with adolescent students, high prevalence of central obesity and hypertension was observed. Central obesity was more frequent in those aged 18 to 20 years, in smokers, and in those that drank alcohol (20).…”
Section: Discussionmentioning
confidence: 94%